Inovasi Media Pembelajaran IPA Smart Book sebagai Upaya Meningkatkan Kemampuan Kognitif Siswa dalam Belajar di MTS Tarbiyah Islamiyah Desa Kedemangan - Anggrini, Rindy Puspita; Ananda, M. Fadhil Raga; Aulia, Mega; Wati, Rahmah; Turnip, Sampe Hamonangan (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
Smart Smart Book is an innovative learning media developed to improve cognition of grade 7 students in a student service program at MTS Tarbiyah Islamiyah Kedemangan Village, Muaro Jambi Regency. This service program includes making Smart Book, implementing the media in the classroom, socializing the use, and sustainable learning activities. Smart Book learning media is applied in the classroom as a tool in delivering material, followed by a quiz as an evaluation of student understanding. The results of the service showed an increase in student enthusiasm and interactivity in the learning process, as well as better cooperation skills between students. Initially, some students lacked collaboration, but over time they began to be active and interact with each other in teams. The success of this program encourages further development by teachers at MTS Tarbiyah Islamiyah, as well as the possibility of implementing it in other classes. This program aims to motivate students to be more enthusiastic in learning and understand the material more easily.